The role of oxidative stress in patients with recurrent pregnancy loss: a review - Vjosa A. Zejnullahu; Valon A. Zejnullahu; Ernad Kosumi (BMC, 2021)
Plain Language summary Recurrent pregnancy loss is a significant health problem in reproductive medicine due to the idiopathic etiology in 50% of cases and limited evidence-based practice. The role of oxidative stress in recurrent pregnancy loss (RPL) is an understudied and enthralling field of investigation. We reviewed the existing information based on the published literature on this complex topic and found that oxidative/nitrosative stress complemented with inefficient antioxidant capacity presents an essential factor in the etiology of recurrent pregnancy loss (RPL). However, based on the currently available knowledge underlying mechanisms through which OS-imbalance affects the increased risk of RPL remains unclear. Future research with a larger number of patients, can provide new insights regarding the molecular mechanisms as well as modifiable factors to decrease OS in this clinical entity.